The use of information and communication technologies in the process of introducing incentive schemes - Nejman, Żaneta; Sadłowska-Wrzesińska, Joanna (Wykorzystanie technologii informacyjno-komunikacyjnych w procesach wdrażania systemów motywacyjnych, 2019)
The most important task for a company should be to invest in the development and awareness of its employees, as well as to understand and appreciate them. Motivated employees who bring knowledge and experience to the company contribute to the company’s efficiency and success. Therefore, the condition for a sustainable competitive advantage in today’s world is the ability to consistently develop the potential of human resources. Progressive globalization, a turbulent environment, and changeability force entrepreneurs to introduce flexible solutions through the use of information and communication technologies in the implementation of incentive systems. Information and communication technologies are an integral part of human life and cover a wide range of information technologies. The main objective of this article is to present the results of research on the effectiveness of individual motivational tools and to assess the impact of dynamically developing information and communication technologies on the formation of motivational systems
Informatyka Ekonomiczna = Business Informatics, 2019, Nr 4 (54), s. 46-59
Keywords: informatyka ekonomiczna